ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PROVIDER XL PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS RIAU KEPULAUAN, BATAM - Bakkara, Arfiyanti; Wibowo, Edwin Agung (University of Riau Kepulauan, 2016)
This research intents to know “Do service quality, and price affect to customer loyalty XL products at the Faculty of Economics, Riau Kepulauan University, Batam?